Beyond Human: Transhumanism’s Challenge in Margaret Atwood’s Oryx and Crake - Senehang, Dipankar (Intellectual Inception: A Multidisciplinary Research Journal of Bhojpur Campus, 2025)
The post-apocalyptic world envisioned in Margaret Atwood’s Oryx and Crake foregrounds the superiority of bioengineered creatures over the human species. The novel questions the imagined bountiful world, where technology serves a human purpose, and destabilizes the notion of confirmed mastery in taming biological limits, projecting a dystopian atmosphere. In this regard, this paper explores the conditions of human beings in a trans human world from a humanist perspective. In doing so, it deals with three specific questions: How does Atwood problematize technological development and trans human culture? Why does the novel underscore the validity of human beings? How does Atwood alarm the threat of trans human species, and what does Atwood consider as an antidote to the burgeoning commodification? To answer these questions, this paper embodies Michel Foucault’s humanist notion of human beings and employs Corliss Lamont’s notion of secular humanism. The paper claims that Oryx and Crake reimagines humans in the trans human world, alarming humans to curtail their technological fascination. Although humans have always surpassed the limits of imagination and have been thoughtful of a better world with the expansion of human to trans human culture, this transposition may lead to the dilapidation of the human species and rupture the evolutionary continuation of human development. The study reveals Oryx and Crake’s cautionary endeavour to disclose humans’ dark future in the days to come if they continue to cultivate human experimentation.